Psicoterapia on line: osservazioni cliniche - Costantino, Ludovica (Il sogno della farfalla, 2021)
This article aims to analyze the limits and validity of online psychotherapy by looking at a therapeutic practice experienced during the lockdown caused by the COVID-19 pandemic. The author, a psychiatrist and psychotherapist trained at the Analisi Collettiva seminars, based on the Human Birth Theory, practiced group and individual online psychotherapy in response to the new extraordinary circumstances. The research group, formed by a group of colleagues, played a fundamental role in debating on the new changes occurring in the psychotherapeutic setting. In this paper, in particular, the author describes the patients’ mood during self-isolation and the psychotherapeutic process by reporting stories and dreams interpretation. The author focuses on the clinical case of a patient affected by anorexia and on the resolution of a significant crisis faced during the online psychotherapy.